2017
DOI: 10.1177/0885066617730571
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Perioperative Management of Patients Undergoing Thoracic Endovascular Aortic Repair

Abstract: Endovascular treatments have become increasingly common for patients with a variety of thoracic aortic pathologies. Although considered less invasive than traditional open surgical approaches, they are nonetheless complex procedures. Patients undergo manipulation of an often calcified aorta near the origin of the carotid and subclavian vessels and have stents placed in a curved vessel adjacent to a perpetually beating heart. These stents can obstruct blood flow to the spinal cord, induce an inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 106 publications
(241 reference statements)
0
28
0
Order By: Relevance
“… 1 It is therefore crucial for clinicians to be familiar to the indications, procedure, and devices, a wide range of complications, and the management of potential complications. 12 …”
Section: Historymentioning
confidence: 99%
See 4 more Smart Citations
“… 1 It is therefore crucial for clinicians to be familiar to the indications, procedure, and devices, a wide range of complications, and the management of potential complications. 12 …”
Section: Historymentioning
confidence: 99%
“…When the FDA approved the use of endovascular grafts for thoracic aortic diseases in 2005, it was limited to repairs of descending thoracic aneurysms, intramural hematoma, and penetrating atherosclerotic ulcer. 9 12 As TEVAR trials and outcomes studies demonstrated the safety of the procedure and decreased mortality and morbidity compared with open thoracic aortic repair, more patients became candidates for the procedure. 2 6 In 2012, FDA expanded graft use on traumatic aortic transection, and then in 2013 for all lesions of the descending thoracic aorta, including Type B dissections.…”
Section: Indications For Thoracic Endovascular Aneurysm Repairmentioning
confidence: 99%
See 3 more Smart Citations